Analisis Fungsi Pengeluaran Pemerintah Terhadap Laju Pertumbuhan Ekonomi Kota Surabaya - Moh. Toriq Alfian; Muhammad Yasin (Universitas 45 Surabaya, 2023)
The realization of economic growth and development cannot be separated from the support of the allocation of funds used to make it happen. These expenditures will increase aggregate spending and increase the level of economic activity in the country (Sukirno, 2004). From this aspect, research was carried out using a qualitative descriptive method originating from the BPS City of Surabaya. The results obtained by the regional budget in the city of Surabaya from 2018 – 2020 have fluctuated. In 2019 the regional budget for the City of Surabaya increased by 26.24% while it decreased in the following year by 22.18%. While in 2019 Surabaya City's GRDP increased by 6.08%, but in 2020 it decreased by 4.85% due to Covid-19.